ROLES OF ENVIRONMENTAL CONDITIONS AND ULTRASONICATION IN RELEASING ORGANIC MATTER FROM BIOLOGICAL ACTIVATED CARBON - Anggreini, Sri; Saputra, Ade Jaya; Sanjaya S, LQ Parulian (Jurnal Teknik Sipil dan Arsitektur, 2026)
Biological activated carbon (BAC) is widely used in drinking water treatment because it combines adsorption on activated carbon with biodegradation carried out by the attached microbial community. However, environmental shifts such as changes in pH, temperature, or physical disturbances may cause previously adsorbed organic matter (OM) to detach from the activated carbon. This phenomenon can increase dissolved organic carbon in treated water and potentially affect downstream processes. This study examined how pH, temperature, and ultrasonication influence the release of OM from BAC. The BAC was extracted using DOC-free tap water under different pH conditions (5.8, 7.0, and 8.6) and temperatures (5°C, 20°C, and 30°C), with and without the application of ultrasonication. After treatment, dissolved organic carbon (DOC) and UV absorbance at 260 nm (UV260) were measured to characterize the released OM. The results show that higher pH promotes OM detachment, with both DOC and UV??? values increasing markedly under alkaline conditions. Temperature also played a strong role; warmer conditions enhanced OM release, indicating that higher kinetic energy and increased molecular mobility facilitate detachment. Ultrasonication consistently intensified the release across all conditions, suggesting that the disruption of biofilms and the reopening of blocked pores contribute to this effect. The findings highlight the sensitivity of BAC to operational changes and underscore the importance of monitoring OM release to maintain the reliability of drinking water treatment systems.